American terrorism trials : prosecutorial and defense strategies - Shields, Christopher A., 1968- (Law and society (New York, N.Y.), 2012)
Since 1980, prosecutors and defense attorneys handling federal terrorism trials have developed politicized strategies and counter strategies unique to terrorism trials, and those strategies have had a significant impact on case outcomes. Moreover, case outcomes were positively impacted by proactive policy changes implemented in the wake of 9/11. Building on structural contextual theory and the hydraulic effect, Shields finds that when prosecutors rely less heavily on highly politicized prosecution strategies, conviction rates increased. In fact, his findings indicate that the more prosecutors.